Tripeptides from Allium subhirsitum L. extracts: Pharmacokinetics properties, toxicity prediction and in silico study against SARS-CoV-2 enzymes and pro-inflammatory proteins - Snoussi, Mejdi; Noumi, Emira; Mosbah, Amor; Redissi, Alaeddine; Saeed, Mohd; Tasleem, Munazzah; Alreshidi, Mousa; Adnan, Mohd; Al-Rashidi, Ayshah; Siddiqui, Arif Jamal; Aouadi, Kaïss; De Feo, Vincenzo; et al. (Cellular and Molecular Biology, 2022)
Developing new prophylactic and therapeutic agents with broad-spectrum antiviral activities is urgently needed to combat emerging human severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Since no available clinically antiviral drugs have been approved to eradicate COVID-19 as of the writing of this report, this study aimed to investigate bioactive short peptides from Allium subhirsutum L. (Hairy garlic) extracts identified through HR-LC/MS analysis that could potentially hinder the multiplication cycle of SARS-CoV-2 via molecular docking study. The obtained promising results showed that the peptides (Asn-Asn-Asn) possess the highest binding affinities of -8.4 kcal/mol against S protein, (His-Phe-Gln) of -9.8 kcal/mol and (Gln-His-Phe) of -9.7 kcal/mol towards hACE2, (Thr-Leu-Trp) of -10.3 kcal/mol and (Gln-Phe-Tyr) of -9.8 kcal/mol against furin. Additionally, the identified peptides show strong interactions with the targeted and pro-inflammatory ranging from -8.1 to -10.5 kcal/mol for NF−κB-inducing kinase (NIK), from -8.2 to -10 kcal/mol for phospholipase A2 (PLA2), from -8.0 to -10.7 kcal/mol for interleukin-1 receptor-associated kinase 4 (IRAK-4), and from -8.6 to -11.6 kcal/mol for the cyclooxygenase 2 (COX2) with Gln-Phe-Tyr model seems to be the most prominent. Results from pharmacophore, drug-likeness and ADMET prediction analyses clearly evidenced the usability of the peptides to be developed as an effective drug, beneficial for COVID-19 treatment.